Flexural behavior of reinforced concrete beam with variation of coated reinforcement - Koh, Zhi Yuan (2016)
Reinforced concrete structure is mainly used in the construction of structures and infrastructures from the beginning of the twentieth century. However, some of reinforced concrete structures have deteriorated excessively within 10 years due to aggressive environmental conditions. Application of coating materials as corrosion resistance have been applied to reduce the corrosion issues throughout the worldwide, thus this study was focus on the effect of variation coated reinforcement on the flexural behaviour of reinforced concrete beam. This study investigates the flexural behaviour of reinforced concrete beam embedded with three different types of coated reinforcement that was epoxy, acrylic latex and natural latex. Generally, the study indicated that epoxy and acrylic latex coated reinforcement did not affect the flexural strength of reinforced concrete beam as they have achieved flexural strength comparable to control beam. However, natural latex coated reinforcement was not suitable as new corrosion resistance material as it will affect the flexural strength of the sample by affecting the bonding strength between reinforcement and concrete. Besides that, the result of the study delineated that reinforced concrete beam embedded with epoxy and acrylic latex coated reinforcement has enhanced the load carrying capacity by 28.78 % and 12.33 % respectively, however reinforced concrete beam embedded with natural latex coated reinforcement has reduced the flexural strength by 8.41 % compared to control beam. This can be concluded that reinforced concrete beam embedded with epoxy coated and acrylic latex reinforcement can performed as effective corrosion materials without affecting the bonding strength between reinforcement and concrete.